Women in the history of medicine - Campos Olazabal, Patricia Julia (2020)
It has been a long time since the first female doctor was recognized as such, and somewhat less since universities were officially admitted to women as medical students. Although at present the academic and working conditions have improved, inequalities are still visible in this field, the subject of this writing.The woman is perceived as a "risk" for job stability and described as unable to bear the stress of working as a doctor.In the present work, a journey is made from ancient times to the present day, we see some features of female doctors in Peru and the phenomenon of "feminization" in Medicine, to finish by providing a brushstroke about the current conditions and trends of the work of the woman as a doctor.